Uniting in Diversity: Multicultural Values in the Clean Tradition of Arjowilangun Village, Malang Regency - Sukmawan, Sony; Listyaningrum, Oktavia (Jurnal Sastra Indonesia, 2025)
Religious and ethnic diversity can trigger conflicts between communities such as intolerance, discrimination, and violence. This indicates that there is a need for strengthening related to the creation of a more tolerant environment and respect for differences of beliefs. Arjowilangun Village consists of various religions that are inevitable from intolerance conflicts. For this reason, it is necessary to study multicultural values so that they can be used as an effort to prevent conflict by promoting a deeper understanding of diversity. This is in accordance with the purpose of this research, which is to explore multicultural values that include the values of democracy, tolerance and harmony which are reflected in a series of village clean traditions in Arjowilangun Village. This research includes qualitative research with a field research approach. This approach was chosen to obtain real data and be able to understand directly the multicultural values contained in the village clean tradition. This study found that the clean tradition of Arjowilangun village was followed by all indigenous people and not Arjowilangun residents. The implementation of this village clean tradition contains very important values for life, namely, the value of democracy, the value of harmony, and the value of tolerance. The value of democracy is reflected in attitudes, namely, the freedom to express and respect differences of opinion during preparatory meetings before the clean tradition of the village is implemented. The value of tolerance appears in the attitude of respecting and respecting the rights of others when the recitation activity is not only followed by certain people, but both parents and school children can participate in the recitation activity The value of harmony that arises in the form of the practice of mutual respect is reflected in the prayer of thanksgiving activities of each religion, mutual cooperation, togetherness shown with all community members involved in the preparation and procession.